FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN PREMENSTRUAL SYNDROME PADA REMAJA DI DKI JAKARTA SELAMA PANDEMI COVID-19 TAHUN 2021 - Nadia Ramadhanty (2021)
Premenstrual syndrome (PMS) is a symptoms combination of physical, psychological, and behavioral changes that occur a week or few days before menstruation. PMS is influenced by many factors. The presence of increased stress in pandemic covid-19 caused physical and emotional discomfort during PMS. The aim is to determine the factors associated with PMS on adolescents in DKI Jakarta during the Covid-19 pandemic year 2021. The study used cross-sectional analytic design. The population is teenagers aged 10-24 years who lived in DKI Jakarta. The sampling technique used convenience sampling method by online used google form. The sample is 294 respondents. The variables were age, age at menarche, education, Body Mass Index (BMI), stress, exercise pattern, and dietary pattern. The bivariate test used chi square test and the multivariate used multiple logistic regression. The bivariate results showed that severe stress (p= 0.000 POR = 6.667 95% CI 3.393-13.097) and exercise pattern (p=0.015 POR = 2.442 95% CI 1.224-4.872) associated with PMS. Based on multivariate analysis, severe stress has the greatest influence on PMS (p= 0.000 POR = 6,483 95% CI 3,268-12,861) after controlled by exercise pattern and BMI variables. Respondents are expected to manage stress well and exercise regularly.